Analysis of Implementation of Infection Prevention and Control at Royal Prima Marelan General Hospital - Fajar Sahputra; Ermi Girsang; Ali Napiah Nasution (Postgraduate, University of Mataram, 2023)
Nosocomial infections or Healthcare-Associated Infections (HAIs) are a serious problem for global public health, including Indonesia. HAIs are infections experienced by patients during treatment and health care procedures â‰¥ 48 hours and â‰¤ 30 days after leaving the health facility. This study aims to analyze the implementation of infection prevention and control at the Royal Prima Marelan General Hospital. This research is a quantitative study with an observational analytical approach with a Cross Sectional Study design, namely in the form of data collection aimed at analyzing the implementation of infection prevention and control at the Royal Prima Marelan General Hospital for the period July to August 2023. The population in this study was 100 people who included hospital management who were considered competent in providing information. The population sample for this study that met the inclusion and exclusion criteria was 50 people. The results of bivariate analysis show that the variables related to infection prevention and control are knowledge, motivation, supervision and workload. The results of multivariate analysis show that the variable that partially influences the prevention and control of nosocomial infections in hospitals is knowledge.